Aksi Mengenal dan Memilih Obat (AMMUBA) di Puskesmas Adiarsa Karawang - Septiani, Dia; Mulki, Munir Alinu; Vriezka Mierza (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2023)
Drugs are an important element in health administration efforts, both preventive, promotive, curative, and rehabilitative. Errors in the selection and use of drugs can cause harm to public health and the environment. Educational actions have been carried out for the community in recognizing and choosing the right medicine, through health facilities at Puskesmas Adiarsa, Kabupaten Karawang. A total of 20 people were persuasively educated and given a pre-test questionnaire and an educational post-test questionnaire to measure the increase in knowledge and understanding. The results of this activity are known to people who are visiting the Puskesmas Adiarsa Karawang increased their understanding by 49% in recognizing and choosing drugs so that it can be said that educational activities to recognize and choose drugs are successful and people are smarter in using drugs.